(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Dendrobium farmeri Paxton, an endangered epiphytic orchid native to Bangladesh is traditionally used for possesses significant traditional medicinal importance. However, its pharmacological potential remains under explored. This study was designed to evaluate the antioxidant, anti-inflammatory and cytotoxic bioactivities of methanolic crude extracts derived from naturally grown plant parts (leaves, pseudo bulbs, roots) and in vitro developed plantlets of D. farmeri. The antioxidant capacity, assessed via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay, revealed that the leaf extract exhibited the highest scavenging efficiency (71.13 ± 0.007% at 250 µg/ml) compared to standard ascorbic acid (80.81 ± 0.003% at 250 µg/ml). Anti-inflammatory potential, determined by the in vitro egg albumin denaturation inhibition assay, demonstrated maximum protection in the leaf extract (54.4 ± 0.17% at 250 µg/ml), while standard acetylsalicylic acid yielded 94.3 ± 0.02% at 250 µg/ml concentration. Furthermore, the Brine Shrimp Lethality Bioassay (BSLA) indicated strong cytotoxic potential across all extracts, with the root extract demonstrating the highest toxicity (LC50 = 32.547 µg/ml) compared to the standard potassium dichromate (LC50 = 16.685 µg/ml). Notably, in vitro derived plantlets also exhibited substantial bioactivities, confirming their viability as an alternative sustainable source for medicinal compounds. These findings provide rigorous empirical validation for the traditional therapeutic uses of D. farmeri and highlight its potential as a natural source for antioxidant, anti-inflammatory and cytotoxic agents, reinforcing the urgent need for its conservation in Bangladesh. Plant Tissue Cult. & Biotech. 36(1): 199-208, 2026 (June)